Performance evaluation of several basic types of DC-DC converters for small-scale wind turbine connected to isolated load - Rizki Mendung Ariefianto; Rini Nur Hasanah; Hadi Suyono; Tri Nurwati; Eduard Muljadi; Hazlie Mokhlis (Institute of Advanced Engineering and Science, 2026)
Small-scale wind turbines (SSWT) encounter a primary issue in power extraction, making the integration of DC-DC converters with maximum power point tracking (MPPT) crucial for performance enhancement. This study focuses on an evaluation of basic DC-DC converters, which offer many benefits when applied to SSWT systems. By considering efficiency, suitability, and electrical stress aspects, six DC-DC converter topologies consisting of boost, buck-boost, SEPIC, Cuk, zeta, and Luo, were tested under perturb and observe (P&O) and incremental conductance (INC) MPPT strategies. A 6.5-kW SSWT system, including a DC-DC converter and MPPT was designed in detail using PSIM. The results show that boost converter demonstrated the best overall performance in terms of power extraction, efficiency, and stress reduction, although its operation was limited to a narrower wind speed range. The zeta converter achieved efficiency and power extraction comparable to the boost converter with stable operation over a broader wind speed range, while the buck–boost converter offered step-up/step-down capability but experienced higher voltage and current stress. The SEPIC and Cuk converters showed low overall performance compared to others, whereas the Luo converter was better suited for low-wind-speed conditions.